The Acceleration Development of Disadvantaged Region: On Government Affairs Perspective - Saptono Jenar (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Building the disadvantaged regions is one of the government's tasks, including local governments. Conditions in the disadvantaged regions require acceleration to continue to be constructed so that it truly becomes the equivalent of other regions in Indonesia. Therefore, it takes approaches in doing so, among them is the welfare approach in the disadvantaged regions. To implement such welfare approaches in the framework of national development, it is necessary to accelerate for disadvantaged regions. Therefore this paper focused about the acceleration development of disadvantaged region: on government affairs perspective. The methods of research used are qualitative methods with literature study techniques or literary studies, documentation, and other descriptive techniques. The results showed that the implementation of the acceleration development of disadvantaged region has high enough urgency to do to realize national goal (staatsidee)..